Rizal makata - Almario, Virgilio S. (Manila Anvil Pub., Inc., 2011)
Rizal as a prolific writer.
Keywords: Rizal, Jose -- 1861-1896 -- Poetry; Philippine poetry (Spanish) -- History and criticism; Philippine poetry (Filipino) -- History and criticism